Assessing the relatonship between students' perception towards group work and their academic achivement - Ahmad, Idris Abidemi Tijani (Institute of Education, International Islamic University Malaysia, 2011)
Group work as one of the student-centered learning strategies characterized under the cooperative learning approach has become a central feature for many colleges' courses. It allows students to work in small groups helping each other to develop questions, hone their problem solving skills, and stimulate them to create something of new substance. With group work students will likely obtain soft skills which incorporate all aspects of interpersonal, academic and non-academic skills, and which serve as pre-requisite to employment in the workplace. In Malaysian context, soft skills are demonstrated to include communicative skills, thinking and problem solving skills, teamwork force, life-long learning and information management, entrepreneur skills, ethical, moral and professionalism, and leadership skills. These skills were proven by several literatures that group work learning strategy can be the best tool to develop them in students. For these profound benefits of group work, the current study sought to explore students' perception at the International Islamic University Malaysia (IIUM) towards learning in group. The researcher also assesses the relationship that exists between students' perception on group work and their academic achievement by using a Pearson correlation analysis. The respondents generally reported a positive perception toward group work learning. With regard to the correlation analysis, there was no significant statistical relationship between students' perception on group work and their academic achievement. However, the study shows a significant difference between low achiever and high achiever students on their self-efficacy to involve in group work. These results warrant further research using more advanced statistical tools to have a broader outlook. Finally, it is hoped that the study will open new avenues to benefit each and every sectors of higher education centres striving to promote high standard of education and professional careers for their students.